Prevalance of nosocomial infection in paediatric intensive care unit at Pietersburg Hospital in Limpopo, South Africa - Makhwanya, Tshimangadzo Mildred (My University, 2021)
Nosocomial infection constitutes a major health problem associated with high morbidity and mortality. This study is aimed at investigating the prevalence of nosocomial infections in paediatric intensive care unit of Pietersburg hospital, Limpopo, South Africa and identify the pathogens responsible for such infections and determine their anti-microbial activity. The study applied a retrospective quantitative descriptive study design to execute the objectives of the study. Convenience sampling was applied to select 98 participants that met the selection criteria to collect the data set from the hospital files between 1st January 2017 to 31st December 2017 in a self-designed template. Results shows that the prevalence of nosocomial infections in children admitted from 1st January 2017–31st December 2017 at Pietersburg hospital was 13.27% where majority were females at 61,5% with the remaining 38,5% being male. Majority of participants that developed HAI were below 24 months of age (69%). Hospital stay was a mean of 23 days. The underlying conditions in participants who developed HAI were mostly HIV in 4 of 13 (31%) and had association with hospital stay (Chi-square = 140,14; pvalue=0,0034). Majority of patients that acquired HAI were admitted for a respiratory condition n=12; (92%) mainly Pneumonia and Bronchiolitis. Potential risks factors for developing HAI were endotracheal intubation, mechanical ventilation; central venous catheter (Chi- square =21,195; p value= 0,0035); Peripheral vascular catheter (Chisquare = 17,106; p-value= 0,0167); urethral catheter (Chi-square = 20,013; p-value= 0,0055) and surgery since admission (Chi-square = 27,649; p-value= 0,0003). There was a strong correlation between hospital stay and mortality rate (r=36%; p- value<0.0001). Klebsiella pneumonia was the most identified pathogen from the respiratory site (50%). Coagulase-negative staph aureus was the most identified organism in the bloodstream. The study found that the development of HAI was associated with increased length of hospital stay and an increased rate of mortality.
Thesis (M.Med. (Paediatrics and Child Health)) -- University of Limpopo, 2021
Keywords: Nosocomial infections; Cultured organisms; Pathogens; Hospital stay; Nosocomial infections in children -- South Africa -- Limpopo; Pediatrics -- South Africa -- Limpopo; Intensive care units